Investigation of Commercially Pure Titanium Structure during Accumulation and Release of Hydrogen by Means of Positron Lifetime and Electrical Resistivity Measurements; Advanced Materials Research : Advanced materials, synthesis, development and application; Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013) - Bordulev Yu. S. Yuri Sergeevich; Laptev R. S. Roman Sergeevich; Kudiyarov V. N. Victor Nikolaevich; Lider A. M. Andrey Markovich (Diagnostics and Engineering of Novel Materials, 2014)
Title screen